2016
DOI: 10.1093/aje/kwv344
|View full text |Cite
|
Sign up to set email alerts
|

Can the Heterosexual HIV Epidemic be Eliminated in South Africa Using Combination Prevention? A Modeling Analysis

Abstract: Little is known about how combining efficacious interventions for human immunodeficiency virus (HIV) prevention could lead to HIV elimination. We used an agent-based simulation model, the HIV calibrated dynamic model, to assess the potential for HIV elimination in South Africa. We examined several scenarios (from continuation of the current status quo to perfect achievement of targets) with differing combinations of male condom use, adult male circumcision, HIV testing, and early antiretroviral therapy (ART). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Mathematical modelling has been used to understand the spread of HIV and compare prevention strategies . Such combination interventions generally include voluntary male circumcision, behaviour change (which generally includes emphasis on detection and treatment of STIs), and ART used as “treatment as prevention” (TaSP) or PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical modelling has been used to understand the spread of HIV and compare prevention strategies . Such combination interventions generally include voluntary male circumcision, behaviour change (which generally includes emphasis on detection and treatment of STIs), and ART used as “treatment as prevention” (TaSP) or PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…One of South Africa’s strategic health objectives is to reduce HIV incidence by 50% by the end of 2016 [ 36 ]. However, to decrease HIV incidence and prevalence over a 50-year time-scale, it has recently been shown that substantial scale-up of combination HIV prevention programs will be required [ 37 ]. Community health workers have been drafted as a priority workforce in South Africa’s approach to re-engineering primary healthcare [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] In September 2016, South Africa removed the CD4 cell count threshold for ART eligibility and adopted the WHO 2015 Universal Test and Treat (UTT) policy, making all HIV positive patients eligible for ART at diagnosis. [15][16][17] Clinical trials showed that, compared with patients who deferred ART, patients who started treatment immediately after HIV diagnosis had lower rates of AIDS-related adverse events and improved viral suppression rates with no difference in post-initiation attrition rates. [18][19][20][21] Moreover, patients who started ART immediately after diagnosis were less likely to transmit HIV than patients who deferred ART.…”
Section: Introductionmentioning
confidence: 99%